Low Altitude Tailing Es (LATTE): Analysis of Sporadic‐E Layer Height at Different Latitudes of Middle and Low Region - Qiong Tang; Chen Zhou; Huixin Liu; Yi Liu; Jiaqi Zhao; Zhibin Yu; Lianhuan Hu; Zhengyu Zhao; Xueshang Feng (Space Weather)
Abstract In this paper, the Earth's sporadic‐E (Es) layer vertical motion is investigated by using an image processing technique for automatic scaling ionograms from Mohe (122.37°E, 53.50°N, dip angle 71°), Beijing (116.25°E, 40.25°N, dip angle 59°), Wuhan (114.61°E, 30.53°N, dip angle 46°) and Fuke (109.13°E, 19.52°N, dip angle 27°). Es traces descend with different periodicities, indicating tidal modulation to Es layers. Comparing winds from a combination of the Ionospheric Connection Explorer/Michelson Interferometer for Global High‐Resolution Thermospheric Imaging and meteor radar measurements with Es layers, we find that Es traces at high altitudes (above 110 km) rapidly move down in accordance with the descent of the wind shear nulls, which indicates the important role of the tides in the formation and descent of the Es layer at high altitude. The lower‐lying Es layers, however, do not descend with the wind shear null, but stay at the bottom of the E region (∼100 km) for a long time, which cannot be explained by tidal wind shear theory. In addition, the time duration of the Es layers staying at low latitudes increases with the decreasing latitude. Simulation results demonstrate that the low altitude tailing Es layer is dominated by the dramatically enhanced collision frequency at the lower height of the mesosphere and the lower thermosphere region.